2012
DOI: 10.1152/japplphysiol.00898.2011
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide modulates hypoxia-inducible factor-1 and poly(ADP-ribose) polymerase-1 cross talk in response to hypobaric hypoxia

Abstract: The physiological response to hypobaric hypoxia represents a complex network of biochemical pathways in which the nitrergic system plays an important role. Previous studies have provided evidence for an interplay between the hypoxia-inducible factor-1 (HIF-1) and poly(ADP-ribose) polymerase-1 (PARP-1) under hypoxia. Here, we evaluate the potential involvement of nitric oxide (NO) in the cross talk between these two proteins. With this aim, we studied comparatively the effect of pharmacological inhibitors of NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 77 publications
2
22
0
Order By: Relevance
“…Martin-Oliva et al [60] were the firstto show that HIF-1-induced suppression of Complex II and Complex IV in deferoxamine-induced hypoxia depends on PARP-1 activation and the PARP-1-mediated production of ROS [61][62][63]. The inhibition of PARP-1 blocks HIF-1 activation and expression of HIF-dependent genes, among them the factor inhibiting HIF (FIH) [64,65].…”
Section: Interaction With Hypoxia-inducible Factors (Hif)mentioning
confidence: 99%
See 1 more Smart Citation
“…Martin-Oliva et al [60] were the firstto show that HIF-1-induced suppression of Complex II and Complex IV in deferoxamine-induced hypoxia depends on PARP-1 activation and the PARP-1-mediated production of ROS [61][62][63]. The inhibition of PARP-1 blocks HIF-1 activation and expression of HIF-dependent genes, among them the factor inhibiting HIF (FIH) [64,65].…”
Section: Interaction With Hypoxia-inducible Factors (Hif)mentioning
confidence: 99%
“…HK dissociates from the mitochondrial surface upon Iduna-mediated PAR efflux from the nucleus [23][24][25], suggesting that PARP activation can in fact uncouple glycolysis and mitochondrial anabolism. Furthermore, HIF activation, that suppresses mitochondria and induces glycolysis (Warburgtype metabolism) and neoplastic transformation, is supported by PARP activation [60][61][62]64,66]. The interaction between the PI3K pathway and PARPs can be implicated in Warburg-type metabolic rearrangements, as PARP inhibitors and PI3K pathway inhibitors can potentiate each other's antitumor activities [75,82].…”
Section: Q6mentioning
confidence: 99%
“…However, the mechanism remains unclear. A report showed that the reduction of NO level and NOS expression prevented (ADP-Ribose) Polymerase 1 (PARP-1) activation (Martínez-Romero et al, 2012). PARP-1 is the key factor to induce the activation of BER (Dziaman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism might be associated with the fact that PlGF depends heavily on the release of endothelial-derived NO,3 and l -arginine improves endothelial function by ameliorating the expression of eNOS and NO, ultimately enhancing myocardial tissue perfusion. Another option could be that l -arginine can also reduce endothelial cell damage under hypoxic conditions, so as to maintain the stability of new blood vessels 9. The last but not the least, possibility might be that the level of asymmetric dimethylarginine, an arginine analog that competes with l -arginine for eNOS, is increased in AMI and can also lead to the impairment of endothelial function, and the competitive inhibition of eNOS by asymmetric dimethylarginine may be reversed by the supplementation of l -arginine 25…”
Section: Discussionmentioning
confidence: 99%
“…Since l -arginine is a substrate for eNOS, its supplementation in animals improves endothelial function 8. This amino acid can also diminish the endothelial cell damage caused by various factors under hypoxic conditions and stimulate angiogenesis 9. However, the therapeutic effects of intramyocardial injection of PlGF combined with oral supplementation of l -arginine have not been investigated.…”
Section: Introductionmentioning
confidence: 99%